Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 21995 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Sphagnum denticulatum Bridel, 1826" ] } The dataset includes 21995 records from 132 constituent datasets: 1 records from Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 45 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 85 records from Herbarium Senckenbergianum (GLM) - Lichenes. 24 records from Moscow University Herbarium (MW). 14 records from The New York Botanical Garden Herbarium (NY). 1 records from Bernice P. Bishop Museum. 3 records from Canadian Museum of Nature Herbarium. 5 records from WTSWW Data: All Taxa (West Wales). 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Herbier du muséum Henri-Lecoq de Clermont-Ferrand - Bryophytes. 49 records from Mosses and Liverworts: Records for Kent.. 1 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 3 records from Biodiversitätsdatenbank des Landes Salzburg. 17 records from Meise Botanic Garden Herbarium (BR). 16 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 1 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 15 records from Marie-Victorin Herbarium (MT) - Bryophytes. 12007 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 27 records from Royal Botanic Garden Edinburgh Herbarium (E). 97 records from National Trust Species Records. 4 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 1 records from Royal BC Museum - Herbarium (V). 819 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas. 47 records from NRW Regional Data: North Wales. 7 records from Universität Salzburg. 8 records from Natural History Museum (London) Collection Specimens. 362 records from LERN Records. 227 records from Miscellaneous records held on the Cofnod database. 6 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 2 records from Universitat de València, Colecciones de Criptógamas: VAL_Briof. 14 records from River Macrophytes Database. 18 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 136 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 1 records from Non-vascular Plants, Outer Hebrides. 6 records from Herbarium Berolinense, Berlin (B). 1 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 246 records from Observation.org, Nature data from around the World. 1 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 3 records from Masaryk University - Herbarium BRNU. 41 records from Long-Term Monitoring Network Vegetation Quadrats. 1 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 9 records from Knoydart Bryophytes, 1990. 81 records from Shropshire Ecological Data Network database. 297 records from Phase Two Lowland Heathland Survey. 358 records from University of Michigan Herbarium. 2 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Plants. 57 records from Isle of Man historical wildlife records 1995 to 1999. 3727 records from Dutch Vegetation Database. 44 records from Bryophytes of Ireland : Data Compiled Post-Atlas. 1 records from HBGBryophyta - Herbarium Hamburgense. 1 records from SER Site-based Surveys. 5 records from The AAU Herbarium Database. 8 records from naturgucker. 33 records from Herbarium (ICEL). 2 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 45 records from North East Scotland Mosses and Liverworts (1950-2014). 12 records from iNaturalist Research-grade Observations. 118 records from Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 6 records from Vascular Plants and Bryophytes of Glen Sligachan. 14 records from Flora of Słowiński National Park, Poland. 10 records from HBRG Fungus, Lichen & Lower Plants Dataset. 14 records from Miscellaneous records held by BIS. 124 records from CSIC-Real Jardín Botánico-Colección de Musgos (MA-Musci). 7 records from Field Museum of Natural History (Botany) Bryophyte Collection. 40 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 13 records from Harvard University Herbaria: All Records. 4 records from HO AVH data. 4 records from All taxa records for Leicestershire and Rutland. 92 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from Montgomeryshire Wildlife Trust records held by BIS. 13 records from Ty Canol National Nature Reserve (NNR) Species Inventory. 8 records from NMNH Extant Specimen Records. 2 records from ICN - Universidad Nacional de Colombia. 1 records from University of Vermont, Pringle Herbarium, North American bryophytes. 16 records from Flora d'Andorra. 1 records from Naturschutzgebiet Sistig-Krekeler-Heide. 2 records from Briòfits d'Andorra. 2 records from Biodiversitätsdatenbank des NP Hohe Tauern. 5 records from Herbario Nacional Colombiano (COL). 6 records from Natural History Museum Rotterdam - Specimens. 281 records from National Trust for Scotland Species Records. 3 records from PlutoF platform reference-based occurrences. 31 records from Moss herbarium, UiB. 12 records from Bryophyte collection. 2 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 2 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 3 records from Bryophytes of Glen Nevis Woods 1987-1988. 1 records from Erzental (Oberotterbach). 199 records from Naturalis Biodiversity Center (NL) - Botany. 13 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 1 records from Standing Waters Database - Scotland. 2 records from Isle of Wight Notable Species. 2 records from Rutgers University, Chrysler Herbarium - Bryophyte Collection. 1 records from National System of Protected Areas in Poland - Plants. 20 records from RECORD Bryopsida Data. 20 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 757 records from Phase 2 Lowland Grassland Survey of Wales. 108 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1 records from Isle of Man historical wildlife records 1990 to 1994. 29 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 56 records from Tropicos Specimen Data. 3 records from TWIC Biodiversity Field Trip Data (1995-present). 2 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 52 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 22 records from International Barcode of Life project (iBOL). 1 records from Cuxhavener Küstenheiden. 16 records from Argyll Biological Records Dataset. 60 records from Leicestershire Bryophyte Data. 273 records from Natural Resources Wales Regional Data : Mid-Wales. 53 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 2 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 7 records from Tullie House Museum Natural History Collections. 53 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 113 records from Duke University Herbarium Bryophyte Collection. 1 records from Plants, Bryophytes and Lichens recorded on the L젡nd Coire Dhorrcail Estate during June 2001.. 5 records from ArtenFinder. 7 records from Herbario de Briófitos de la Universidad de Salamanca: SALA-Bryo. 2 records from Collections and observation data National Museum of Natural History Luxembourg. 13 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 15 records from MEXU/Colección de Briofitas. 62 records from Phase 2 Lowland Peatland Survey of Wales 2004 onwards. 1 records from CeDoc de Biodiversitat Vegetal: BCN-Bryophyta. 8 records from CANB AVH data. 3 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 3 records from Natural History Museum, University of Tartu. 67 records from National Inventory of Swiss bryophytes. 11 records from NBIS Records to December 2016. 2 records from ANTARCTIC PLANT DATABASE. 2 records from Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 18 records from Ireland's BioBlitz. 20 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 1 records from Naturhistorisches Museum Mainz, Herbarium von Ruprecht Düll. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences